A hybrid fracture-micropore network model for multiphysics gas flow in coal. (1st December 2020) - Jing, Yu; Rabbani, Arash; Armstrong, Ryan T.; Wang, Junjian; Mostaghimi, Peyman
Graphical abstract: Highlights: A novel hybrid Fracture-Micropore Network Model (FM-PNM) is developed for coal. FM-PNM is able to model multiphysics gas flow in both coal matrix and fractures. The model can be applied for CSG simulations and predicting GHG emission of coal mines. Abstract: Coal is not only a combustible black sedimentary rock, but also a source and reservoir rock for natural gas, known as coal seam gas (CSG). A thorough understanding of gas transport through coal matrix micropores as well as coal cleats is of significance in both mining and CSG industries. Multiple physical mechanisms are identified during gas flow in coal. However, there is not a comprehensive modelling framework, where multiscale flow behaviours with multiphysics are coupled. In this paper, we develop a hybrid Fracture-MicroPore Network Model (FM-PNM), coupling viscous gas flow in fractures and gas diffusion in coal matrix. This model includes multiphysics gas flow mechanisms in coal, including gas sorption, diffusion, slip flow, and compressibility. With FM-PNM, methane flowing through fractured coal is simulated to compute apparent permeability and gas flow rates, which are critical for CSG developments. Besides, the process of gas emission from coal over time is simulated, where desorption curves are obtained and analysed at different scenarios. This multiphysics FM-PNM gives a promising framework for studying gas flow in fractured coal, which can be integrated with other works to study different coal internal structures, flow models and stress conditions. This model has a wide range of applications, including prediction of greenhouse gas (GHG) emission of coal mines, ventilation design during mining, CSG development, and CO2 storage management.